2009
DOI: 10.1097/ccm.0b013e31819cf050
|View full text |Cite
|
Sign up to set email alerts
|

Experience of diffusion tensor imaging and 1H spectroscopy for outcome prediction in severe traumatic brain injury: Preliminary results*

Abstract: FA and NAA/Cr hold potential as quantitative outcome-prediction tools at the subacute phase of TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 35 publications
2
83
2
Order By: Relevance
“…[4][5][6] However, for these results to be widely applicable, quantitative MRI methods must account for hardware and software disparities within and across institutions. The goal of the current study was to develop and validate, as a first step, an algorithm based on DTI for outcome prediction in severe TBI in a multicenter setup after implementation of a normalization process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] However, for these results to be widely applicable, quantitative MRI methods must account for hardware and software disparities within and across institutions. The goal of the current study was to develop and validate, as a first step, an algorithm based on DTI for outcome prediction in severe TBI in a multicenter setup after implementation of a normalization process.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-eight patients and 15 controls described in a previous study 6 were used as a validation dataset. MRI examinations were performed using the same DTI acquisition parameters but on a different MRI unit.…”
Section: Independent Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study did not yield any correlations between CBF changes and memory and learning impairment, but poor performance in the Morris water maze was found to correlate with enhanced thalamic vessel density (r = -0.81, p < 0.01). The thalamus is often found to be damaged in moderate and severely injured TBI patients as well as in animal models (Pierce et al 1998, Maxwell et al 2004, Tollard et al 2009, Little et al 2010, but the role of the thalamic pathology in epileptogenesis after acquired etiologies like TBI is poorly understood (Bonilha et al 2004, Blumenfeld et al 2009). We also found that a high vessel density in the ipsilateral thalamus was associated with increased CBF and enhanced seizure susceptibility in injured rats.…”
Section: Correlation Of Mri Findings With Cognitive Deficits and Hypementioning
confidence: 99%
“…3,4 Because of the central role of the thalami in many physiologic systems, it is not surprising to find an increasing number of studies using a variety of different MR imaging modalities (conventional volumetric assessment, magnetization transfer, MR spectroscopy, and diffusion tensor imaging) that demonstrate the central role of thalamic involvement in the pathophysiology of various pathologic conditions (including multiple sclerosis, schizophrenia, and head trauma, to name a few). [5][6][7] In particular, thalamic involvement is becoming increasingly recognized as a significant step in the development of clinical disability and memory impairment in multiple sclerosis. 8 Tovar-Moll et al 9 in an article published in the current issue of the American Journal of Neuroradiology demonstrate thalamic abnormalities in diffusion tensor metrics that correlate with clinical disability scores, in keeping with similar studies published on the subject.…”
Section: 2mentioning
confidence: 99%